USING KEYS AS COMPETENCY-ORIENTED ASSIGNMENTS - Qo’qonboyeva Shaxlo Rafikjonovna; Ergashev Azamjon Anvarjon o’g’li; Yasharova Elnoraxon O’ktamjon qizi (International Journal of Innovations in Engineering Research and Technology, 2022)
This article used keys as competency-oriented assignments, and carried out scientific research according to the research of Modern teachers.